XVI HSE April International Academic Conference on Economic and Social Development. Section 'Science and Innovation' (April 8–10, 2015) - Нет Нет (Foresight and STI Governance, 2015)
Cross-country competition and cooperation in research and innovation are the key concerns of current science and technology (S&T) policy. To provide a broad public discussion of these issues, the HSE ISSEK organized several round tables and seminars as part of the XVI HSE April Conference. Participants considered new approaches to prepare Russia’s long-term S&T forecast, the outputs of Foresight studies in healthcare, fuel and energy, aerospace and water industries, and discussed the practicalities of establishing an HSE-based international Foresight network. The preliminary results of the HSE project that studies the impact of technology on society were presented. A special seminar held under the auspices of an OECD working group focused on cooperation between universities, businesses and public authorities in research, education, and innovation. Another discussion focused on Horizon 2020, the EU Framework Programme for research and innovation development which started in 2014 and is open to research institutions from third countries. Finally, new approaches to building regional innovation systems were scrutinized, including ‘smart specialization’, the impact of local conditions on the effectiveness of research and innovation activities, and effective practices of interaction between authorities of different levels. Presentations were made by representatives of George Washington University (US), OECD, UN Economic Commission for Europe, National Institute for Science and Technology Policy (NISTEP, Japan), Centre for Social Innovation (Austria), The Ministry of Education and Science of the Russian Federation, Russian Science Foundation, Russian Academy of Sciences, Moscow Government, Bank for Development and Foreign Economic Affairs (Russia), Russian Venture Company, Higher School of Economics (Russia), and other organizations.